An unexpected large Crested Tinamou (Eudromia, Tinamidae, Aves) near to Last Glacial Maximum (MIS 2, late Pleistocene) of the Argentine Pampas. (15th March 2020) - Cenizo, Marcos; Noriega, Jorge; Diederle, Juan; Soibelzon, Esteban; Soibelzon, Leopoldo; Rodriguez, Sergio; Beilinson, Elisa
ABSTRACT: A large nearly complete specimen of a Crested Tinamou ( Eudromia, Tinamidae, Aves) is described. It was collected at 'Nicolás Vignogna III' Quarry in Marcos Paz County (Buenos Aires Province, Argentina), coming from near the top of a succession assigned to the Lujanian Stage. Radiocarbon dates constrain the age of the fossil bearing lithosome to the late Pleistocene – early Holocene, including the complete geochronological interval assigned to MIS 2. The new fossil specimen of Eudromia from Marcos Paz exceeds the size range of living species of the genus; but it is osteologically almost indistinguishable from them. Based on the lack of conclusive morphological and metrical differences with modern Eudromia spp., its specific status is not definitely ascertained in this contribution, being considered as a probable large morph of E. elegans . Crested tinamous are inhabitants of open and xeric environments with warm temperate to cold temperate climatic conditions. The fossil location is more than 250 km east of the eastern distributional limit of the nearest extant species. This geographical outlier could be tentatively associated with the expansion of arid or semiarid paleoenvironments typical of the Central or Patagonian domains over the temperate Pampean grasslands during the MIS 2 times.